Outcomes of paediatric malarial hepatopathy: a study from Eastern India - Subal Ku. Pradhan; Pawan Mutalik; Tirumal Subudhi; Arakhita Swain; Niranjan Mohanty (Paediatrica Indonesiana, 2014)
Background Severe malaria causes multi-organ involvement ,including hepatic dysfunction.Jaundice in severe malaria is foundmore commonly in adults than in children. It is important toassess the factors associated with malarial hepatopathy, the variedclinical presentations, as well as the complications in order toinitiate early interventional measures. There are a limited numberof studies in the pediatric population on malarial hepatopathy.Objective To assess the factors associated with malarialhepatopathy, the varied clinical presentations, as well as itscomplications.Methods This prospective study was conducted in the Departmentof Paediatrics, Sardar Vallabh Bhai Patel Post Graduate Institute ofPaediatrics (SVPPGIP), Cuttack, Odisha, India from January 20 10to June 2013, and included 70 children with malaria and jaundice,aged 6 months to 14 years. Malaria was confirmed by microscopicexamination of blood smears. Detailed clinical evaluations andinvestigation s were carried out to find multi-organ afflictions,with a special emphasis on hepatic involvement.Results Of218 children with malaria admitted during this period,70 (32%) children had fever and jaundice on presentation. Allchildren who had both Plasmodium faldparum and vivax infectionhad malarial hepatopathy. Complications, including acutekidney injury (AKI), disseminated intravascular coagulation(DIC), cerebral malaria, and mortality, were significantlyhigher among children with malarial hepatopathy compared tochildren without hepatopathy. Howevei; there was no significantdifference of hypoglycemia, respiratory distress syndrome (RDS),convulsions or severe anemia, between children with and withouthepatopathy.Conclusion Hepatopathy is more common with mixed malariainfections. The incidence of AKI, DIC, cerebral malaria, andmortality are significantly higher in patients with hepatopathy.Malarial hepatopathy should be considered in patients presentingwith acute febrile illness and jaundice so that specific treatmentcan be initiated early to prevent increased morbidity and mortality.